Effect of concentration and temperature on the rheological behavior of camu-camu pulp (Agroindustrial Science, 2022)
The objective of this study was to understand how the concentration of soluble solids (Cp) and temperature (Tp) affected the rheological behavior of camu-camu pulp. Factors of Cp (10 – 20 °Brix) and Tp (30 – 60 °C) were varied according to a 3 × 7 factorial design with three repetitions. Ripe camu-camu fruits showed biometric characteristics of weight (10.81 g), axial diameter (2.55 cm), and equatorial diameter (2.68 cm) before being pulped. Physicochemical characteristics of the pulp were: soluble solids (6.26 °Brix), pH (3.46), moisture (92.56%), and ascorbic acid (1.78 g/100 g). Pulp concentration was performed in a rotary evaporator and rheological measurements were evaluated in a Brookfield viscometer. The rheological parameters helped to calculate the consistency index (K: 11.82 to 69.29 Pa·sn) and flow index (n: 0.303 to 0.347) using the Power Law model (R2 > 0.9), revealing the nature of the shear thinning (pseudoplastic behavior). The activation energy varied from 8.51 to 10.21 kJ/mol. The rheological results of concentrated camu-camu pulps can be used as parameters for quality and dimensioning equipment, pipes, heat exchangers, filters, and pumps.
Keywords: Myrciaria dubia; soluble solids; pseudoplastic fluid; consistency index; activation energy